Transkulturel kunsthistorie. Om epistemologi og appropriation af japansk kunst i Danmark: Transkulturel kunsthistorie. Om epistemologi og appropriation af japansk kunst i Danmark - Ravn Borggreen, Gunhild (Periskop – Forum for kunsthistorisk debat, 2022)
The article discusses transcultural art history with Danish examples about Japanese art. This includes an introduction to the concept of transculturation, and how the concept is used in art history research. The core of the argument concerns two interrelated aspects of Danish art historiography: the role of ethnography and the myth of modernism as a Western phenomenon. For the first of these aspects, I analyse the only existing Japanese art history in Danish language, published in 1885. For the other aspect, I analyse recent interpretations of the Danish painter Anna Ancher and her alleged use of formal elements from Japanese woodblock prints. I thereby wish to connect the theoretical issues of transculturation with analyses of transformative and constituent exchange of objects, phenomena and ideas, and point out the potential of the concept of transculturation as both theory and method. An investigation of transcultural connections between Japan and Denmark will contribute to writing a new art history on global interactions.